Analisis Fundamental Makro, Struktur Kepemilikan, Fundamental Mikro Terhadap Nilai Perusahaan Dengan Manajemen Laba, Kinerja Keuangan dan Karakteristik Perusahaan Pada Perusahaan Sub Sektor Pertambangan Yang Terdaftar Bursa Efek Indonesia 2018-2023 - Arfindo Hermawan; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to analyze whether there is an influence of Macro Fundamental Analysis, Ownership Structure, Micro Fundamentals on Company Value with Profit Management, Financial Performance and Company Characteristics in Mining Sub Sector Companies Listed on the Indonesian Stock Exchange 2018-2023. The research used in the research is quantitative method research. The type of data used in this research is secondary data obtained from searching and reviewing annual reports of mining companies listed on the BEI (Indonesian Stock Exchange) for the period 2018 - 2023 via the official website www.idx.co.id, the company's official website, and use supporting journals related to this research. The samples used were 6 mining companies selected using a purposive sampling method, then processed or analyzed using the Smart-PLS version 4 application. The results of this research show that Micro Fundamentals have no significant effect on Company Characteristics, while Macro Fundamentals and Ownership Structure have a significant effect. on Company Characteristics. Micro Fundamentals and Ownership Structure do not have a significant influence on Financial Performance, while Macro Fundamentals have a significant influence on Financial Performance. Macro Fundamentals, Micro Fundamentals and Ownership Structure do not have a significant effect on Earnings Management. Macro Fundamentals, Micro Fundamentals, Company Characteristics, Financial Performance, Earnings Management and Ownership Structure do not have a significant effect on Company Value.